Flexural Performance of Ambient‐Cured Metakaolin‐Stabilized Compressed Earth Brick Walls With Cement‐Soil Mortar Joints - Edmond Didier Medongou Tejiogho; Christopher Kanali; François Ngapgue; Isaac Fundi Sanewu (Engineering Reports)
ABSTRACT This study investigates the flexural performance of metakaolin‐stabilized compressed earth brick (CEB) walls with cement‐soil mortar joints, focusing on their potential as sustainable materials in regions prone to lateral loads. While metakaolin‐stabilized CEBs offer sufficient compressive strength for infill applications, the flexural strength of the walls is critical for resisting lateral forces. The bond between the CEBs and the mortar plays a key role in this strength. The research aimed to optimize this bond by determining the appropriate cement‐soil mortar mix and metakaolin (MK) content for stabilization. Stabilization levels were represented as CEB_MKX, with metakaolin replacement percentages (X) ranging from 0% to 19%, in increments of 2%. Five CEB samples for each metakaolin content were tested for physical, mechanical, and thermal properties according to WD‐ARS 1333 Edition, 2018. The optimum metakaolin content was found to be 11%, with the best cement‐soil mortar mix at a ratio of 1:0.75:5.25, based on 28‐day compressive strength tests in accordance with BS EN 998–2. Walls made with metakaolin‐stabilized CEBs (Characteristic flexural strength, fxk = 0.43 ± 0.02 MPa) showed a 79.17% improvement in flexural strength (under four‐point loading of five samples) compared to unstabilized bricks walls (fxk = 0.24 ± 0.01 MPa), meeting and exceeding the standards set by British 5628, 2005 for lateral load resistance. Strain gauges and Linear Displacement Transducers were used to measure strain and deflection at the mid‐height of the walls during testing. This research supports the development of design guidelines for eco‐friendly stabilized earth bricks, promoting sustainable building solutions.